Could sports biomechanics provide the missing pieces to the talent identification and development puzzle? - Glazier, P. S. (Routledge handbook of talent identification and development in sport, 2017)
In this chapter, I examine some of the main issues that have prevented biomechanics from occupying a more central role in TID in sport and discuss if, and how, these impediments may be overcome. I begin, however, by critically examining how technical skill has been assessed in TID programmes adopted by different sports organisations and scientific investigations ofTID in sport, before arguing a case for the inclusion of a biomechanical component. As there is now a plethora of excellent texts on biomechanical data collection methods and procedures (e.g., Payton & Bartlett, 2008; Robertson, Caldwell, Hamill, Kamen, & Whitdesey, 2013; Winter, 2009), the theory and practice of capturing valid and reliable kinematic, kinetic, and electromyographic data will not be covered here. Interested readers are also directed to Wade and Berg (1991) and Knutzen and Martin (2002) for special consideration of biomechanical measurement issues specifically related to the study of movement in children.